2011
DOI: 10.1371/journal.pone.0017693
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte Microbiome Diversity in Micropropagated Atriplex canescens and Atriplex torreyi var griffithsii

Abstract: Microbial diversity associated with micropropagated Atriplex species was assessed using microscopy, isolate culturing, and sequencing. Light, electron, and confocal microscopy revealed microbial cells in aseptically regenerated leaves and roots. Clone libraries and tag-encoded FLX amplicon pyrosequencing (TEFAP) analysis amplified sequences from callus homologous to diverse fungal and bacterial taxa. Culturing isolated some seed borne endophyte taxa which could be readily propagated apart from the host. Microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 72 publications
1
52
0
3
Order By: Relevance
“…This indicates that the DNA extraction procedure introduces significant bias, thereby influencing the interpretation of the microbial community observed. PCR-based metagenomic approaches such as DGGE Ramond et al, 2013), t-RFLP (Sessitsch et al, 2012;Ding et al, 2013) and next generation sequencing (Gottel et al, 2011;Lucero et al, 2011;Ìnceoğlu et al, 2011;Molina et al, 2012) are continuously used to elucidate the structure and ecological roles of plant-associated (and other) microbial communities. However, few, if any, of these studies share the same DNA extraction protocol and/or are preceded by an evaluation of DNA extraction procedures to select the most efficient.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the DNA extraction procedure introduces significant bias, thereby influencing the interpretation of the microbial community observed. PCR-based metagenomic approaches such as DGGE Ramond et al, 2013), t-RFLP (Sessitsch et al, 2012;Ding et al, 2013) and next generation sequencing (Gottel et al, 2011;Lucero et al, 2011;Ìnceoğlu et al, 2011;Molina et al, 2012) are continuously used to elucidate the structure and ecological roles of plant-associated (and other) microbial communities. However, few, if any, of these studies share the same DNA extraction protocol and/or are preceded by an evaluation of DNA extraction procedures to select the most efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported the occurrence of those species in other plants, including banana (Cao et al, 2002), Aegle marmelos (Gond et al, 2007), Coffea Arabica L. (Fernandes et al, 2009), tangerine andlemons (Dini-Andreote et al, 2009), Deschampsia antarctica Desv. (Rosa et al, 2009), Huperzia serrata (Wang et al, 2011), Bletilla ochracea (Tao et al, 2008), wheat (Smit et al, 1999), Atriplex canescens (Lucero et al, 2011), and Artemisia species (Huang et al, 2009). The group of Pleosporaceae represented by Alternaria species consists mainly of saprophytes that are commonly found in soil or on decaying plant tissues; however, some of them were reported to acquire pathogenic traits (Thomma, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly cultivable, this genus was only detected in this study by clone sequencing and appropriate media should be optimized to isolate and culture this genus in date palm. Cladosporium species are commonly found in many other plants (both herbaceous and woody) and in soil (Arx, 1949;Fisher et al, 1995;Taylor et al, 1999;Bensch et al, 2010), including wheat (Smit et al, 1999), pharmaceutical plants (Heterosmilax japonica) (Gao et al, 2005), and Atriplex canescens (Lucero et al, 2011) where they constitute an extremely large and important genus of plant pathogens. However, Cladosporium also includes cosmopolitan and ubiquitous saprotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis between the endophytic microbial communities of Atriplex canescens and A. torreyi, two halophilic plants used as forage in North America, revealed the presence of distinct communities between the two species, mostly differing in the prevalence of diazotrophic bacteria (Lucero et al, 2011). That finding was directly related to the metabolic differences observed between the two plant genotypes, which can also account for changes observed in plants from distinct genotypes within the same species (i.e., varieties, cultivars).…”
Section: Drivers Of Plant-associated Microbial Communitiesmentioning
confidence: 99%